EP155/#329 Deep cervical injection: a novel technique to increase bilateral sentinel lymph node detection rate in endometrial cancer patients with indocyanine green (TRSGO-SLN-008). (4th December 2022) - Vatansever, Dogan; Altin, Duygu; Giray, Burak; Taskin, Salih; Donmez, Emin; Tokgözoglu, Nedim; Guler, Abdul Hamid; Tasci, Tolga; Bese, Tugan; Turan, Hasan; Kahramanoglu, Ilker; Yalcin, Ibrahim; et al.
Abstract : Objectives: Lymph node assessment provides information that may influence decisions regarding adjuvant treatment in endometrial cancer patients. However, systematic lymphadenectomy may cause significant morbidity. In recent years, the use of sentinel lymph node (SLN) mapping with indocyanine green (ICG) has been accepted to avoid the morbidity of lymphadenectomy. We aimed to assess the diagnostic accuracy of a novel injection technique in detection of sentinel lymph nodes in women with endometrial cancer. Methods: A total of 214 patients with endometrial cancer underwent sentinel lymph node mapping using ICG. ICG was injected into the uterine cervix at the 3 and 9 o'clock positions, submucosally and to the level of junction between uterine cervix and isthmus in group 1(n=107) and to the uterine cervix at the 3 and 9 o'clock positions according to conventional Memorial Sloan Kettering algorithm in group 2(n=107). All the patients in group 2 selected by propensity matching. None of the patients underwent a re-injection neither in group 1 nor group 2. Results: There was no significant difference between baseline characteristics of two groups. The groups were similar in terms of stage, type of tumor, BMI and lymphovascular space invasion. The bilateral detection rates were 94.4% and 76.6% in group 1 and group 2, respectively (p=0.003). No lymph node or lymphatic vessels were identified in only one patient with a history of chronic lymphocytic leukemia in group 1. Conclusions: Deep cervical injection technique significantly increases bilateral SLN detection rate in endometrial cancer patients.